A technical guide to tDCS, and related non-invasive brain stimulation tools. Issue 2 (February 2016) - Woods, A.J.; Antal, A.; Bikson, M.; Boggio, P.S.; Brunoni, A.R.; Celnik, P.; Cohen, L.G.; Fregni, F.; Herrmann, C.S.; Kappenman, E.S.; Knotkova, H.; Liebetanz, D.; et al.
Highlights: A review of technical aspects of transcranial electrical stimulation (tES) techniques. Recommendations for safe and replicable application of tDCS and other tES methods. Discussion of state-of-the-art methodology and design considerations in tES. Abstract: Transcranial electrical stimulation (tES), including transcranial direct and alternating current stimulation (tDCS, tACS) are non-invasive brain stimulation techniques increasingly used for modulation of central nervous system excitability in humans. Here we address methodological issues required for tES application. This review covers technical aspects of tES, as well as applications like exploration of brain physiology, modelling approaches, tES in cognitive neurosciences, and interventional approaches. It aims to help the reader to appropriately design and conduct studies involving these brain stimulation techniques, understand limitations and avoid shortcomings, which might hamper the scientific rigor and potential applications in the clinical domain.